1997
DOI: 10.1089/cbr.1997.12.47
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Growth of Cultured Malignant Cells by Allomelanins, Plant-produced Melanins

Abstract: Allomelanins, which belong to the melanins produced by higher plants and fungi, were studied with respect to their growth suppressive effects on cultured HCT-15 cells derived from human intestinal carcinoma and Meth/A cells derived from a Balb/C mouse lymphoma. Allomelanins were extracted from black soy beans and black sesame seeds with 0.2% NaOH in water. Proteins bonded to the allomelanins were removed by boiling the extracts for 20 hours in 30% NaOH. Although native allomelanins conjugated with protein did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Although pyrolysis-GC-MS has been used to some success for melanin identification and structural analysis [17], most melanin preparations are contaminated with proteins [29]. We have found that purified proteins, due to their content of aromatic amino acids, give thermal degradation product signatures similar to that of plant melanin but degradation product yield is less than 10% of that seen with melanin (data not shown).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although pyrolysis-GC-MS has been used to some success for melanin identification and structural analysis [17], most melanin preparations are contaminated with proteins [29]. We have found that purified proteins, due to their content of aromatic amino acids, give thermal degradation product signatures similar to that of plant melanin but degradation product yield is less than 10% of that seen with melanin (data not shown).…”
Section: Discussionmentioning
confidence: 84%
“…Although melanin has been identified previously within plants [29] the functional role of this polymer is not known. The dramatic increase in the immunostimulatory activity of alfalfa sprout melanin following exposure to an elicitor of plant defensive mechanisms suggests that some structural feature of this molecule has been altered.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Kamei et al . showed that protein‐free allomelanins extracted from black soya beans and black sesame seeds, suppressed the growth of HCT‐15 cells (a cultured human intestinal carcinoma cell line) and Meth/A cells (generated from a Balb/C mouse lymphoma) . Subsequent work by the same group using flow cytometry studies showed that the addition of a high concentration of protein‐free allomelanins (400 mg/ml) to HCT‐15 culture medium blocked the S phase of the cell cycle .…”
Section: Health Effects Of Melaninmentioning
confidence: 99%
“…In the recent years, there is a revival interest in the use of natural pigments in food, cosmetic, and pharmaceutical industries. Melanins are a kind of pigments in all living kingdoms (Senesi and others 1987; Butler and Day 1998), possessing versatile biological activities including antioxidant (Hung and others 2002; Tu and others 2009), radioprotection (Hill and others 1987), antitumor (Kamei and others 1997), anti‐HIV (Montefiori and Zhou 1991), immunostimulating (Sava and others 2001), and antiinflammatory (Mimura and others 1987). Based on these features, melanins have a high potential for use as natural colorants.…”
Section: Introductionmentioning
confidence: 99%